Technical and Economic Evaluation of Local Monitoring Systems for Railway Emergencies - Kh.K. Zukhriddinov (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Railway structures, such as bridges and viaducts, are critical components of transportation infrastructure. Specific Background: These structures are particularly susceptible to damage from natural hazards including earthquakes, mudflows, landslides, and subsidence, posing risks to safety and economic stability. Knowledge Gap: Despite their vulnerability, there is a lack of integrated evaluations addressing both the technical performance and economic efficiency of local real-time monitoring and early warning systems for these assets. Aims: This study aims to assess the technical and economic effectiveness of localized monitoring systems designed for railway structures under emergency conditions. Results: The analysis demonstrates that such systems significantly improve structural risk detection and operational response time, while offering cost-effective solutions for infrastructure management. Novelty: Unlike prior research, this work integrates technical diagnostics with a cost-benefit evaluation, providing a holistic framework for monitoring system implementation. Implications: The findings support the deployment of real-time monitoring as a strategic investment, enhancing resilience and ensuring the continuity of railway operations in hazard-prone regions. Highlights: Real-time monitoring enhances early detection of structural vulnerabilities. Integrated assessment reveals both technical and economic benefits. Critical for risk mitigation in disaster-prone transportation networks. Keywords: Railway Structures, Real-Time Monitoring, Early Warning Systems, Infrastructure Safety, Economic Efficiency